Biosynthesis and characterization of co and ter-polyesters of polyhydroxyalkanoates containing high monomeric fractions of 4-hydroxybutyrate and 5-hydroxyvalerate via a novel PHA synthase. (May 2019) - Lakshmanan, Manoj; Foong, Choon Pin; Abe, Hideki; Sudesh, Kumar
Abstract: Polyhydroxyalkanoates (PHAs) are a group of microbial polyesters that are widely studied due to their versatile physicochemical and mechanical properties. The biosynthesis of PHAs is governed by the enzyme PHA synthase. We have previously reported the discovery of a novel wide substrate specificity PHA synthase isolated from a mangrove environment. In this study, we report the biosynthesis, via the novel PHA synthase, of various PHA co- and terpolymers containing 4-hydroxybutyrate (4HB) and 5-hydroxyvalerate (5HV) monomers, which are lipase degradable. The biosynthesized polymers have varying 4HB and 5HV contents between 5 and 70 mol % depending on the concentration of precursor compounds used. All the polymers exhibit low melting temperature ( T m ) and crystallinity and elastomeric behaviour due to high 4HB and 5HV monomer contents. Supplementation of crude palm kernel oil (CPKO) as carbon source with appropriate precursors enabled the biosynthesis of interesting terpolymers and copolymers containing 3-hydroxyhexanoate (3HHx) along with 5HV and/or 4HB monomers. Lipase degradation assays indicated that co- and ter-polymers containing 4HB and 5HV monomers were successfully hydrolysed by various lipases, but addition of 3HHx monomers in the polymer chain reduced its degradability. These properties of the polymers suggest potential uses as biomaterials. Highlights: A novel PHA synthase isolated from mangrove soil metagenome was used to produce PHA co- and ter-polyesters containing 4HB and 5HV monomers. Monomer contents of 4HB and 5HV could be incorporated up 70 mol % in the biosynthesized polymers. The polymers showed low melting temperature ( T m ) and crystallinity, soft and elastomeric behaviour in the presence of high 4HB and 5HV monomer contents. The monomer composition could be easily tuned by varying the carbon source and co-supplementation of suitable pre-cursors. The polymers showed variable degradability towards lipase enzymes suggesting potential use as biomaterials.